1991
DOI: 10.21273/hortsci.26.6.705c
|View full text |Cite
|
Sign up to set email alerts
|

Birch Seedling Response to Irrigation Frequency and a Hydrophilic Polymer Amendment in a Container Medium

Abstract: European birch (Betula pendula Roth) seedlings (1+ 0 plugs) were planted in a container growth medium amended with 0, 1.2, 2.4, or 3.6 kg/m3 of a commercial hydrogel and watered either daily or once every 3 or 5 days. When hydrogel was incorporated in the growth medium, shoot and root dry weights and lea area were reduced by 19, 29 and 18%, respectively, compared to controls. Shoot height, stem diameter and shoot:root ratio were unaffected by hydrogel ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Throughout the experiment, no effects (P > 0.05) resulting from stress day were found, and there were no interactions between irrigation frequency and stress day. Similar results have been reported for both herbaceous and woody ornamentals (Chu et al, 1995;Jaimez et al, 1999;Tripepi et al, 1991). Tripepi et al (1991) found daily irrigation increased g s among Betula pendula Roth seedlings compared with 3-or 5-d irrigation frequencies.…”
Section: Resultssupporting
confidence: 87%
“…Throughout the experiment, no effects (P > 0.05) resulting from stress day were found, and there were no interactions between irrigation frequency and stress day. Similar results have been reported for both herbaceous and woody ornamentals (Chu et al, 1995;Jaimez et al, 1999;Tripepi et al, 1991). Tripepi et al (1991) found daily irrigation increased g s among Betula pendula Roth seedlings compared with 3-or 5-d irrigation frequencies.…”
Section: Resultssupporting
confidence: 87%
“…This resulted in a signifi cant substrates × polymer interaction. Several authors have reported signifi cant decreases in θ a following hydrogel addition (Flannery and Busscher, 1982;Fonteno and Bilderback, 1993;Heiskanen, 1995;Tripepi et al, 1991). Signifi cant increases in θ a after hydrogel addition have not been reported so far, but their aggregative action, due to their absorption properties, might be involved (Rivière et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophilic polymers could disrupt the normal root-distribution pattern, confining growth to the surface layers of soil. Some results indicated a negative effect on shoot growth (Callaghan et al 1988), suggesting that this was due to a poly-mer-induced increase in the export of assimilate from the shoot to the root, while others refer no significant effect or even a decrease in root growth in response to polymer (Tripepi et al 1991). It seems that the negative synergetic effect of Gel 3 Myc may then be due to a higher root demand altering the direction of growth.…”
Section: Ceratonia Siliquamentioning
confidence: 99%